Synthesis and Catalase Mimic Activity of MnO2 Nano Powder Prepared by Hydrothermal Process (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Manganese dioxide (MnO2) nanopowder has been synthesized by hydrothermal method. MnO2 was annealed at different temperatures (250, 400, 550, 700˚C). The crystal structure and surface morphology of these nanostructures were characterized by X-ray diffraction (XRD), Atomic Force Microscope (AFM) and Scanning Electron Microscopy (SEM). The catalase mimic activity (catalytic activity) of MnO2 against hydrogen peroxide (H2O2) was studied by using the new method and found that 400˚C is the best annealing temperature.